Characteristics of Calvaria Depression Fractures Patients in Dr. Kariadi General Hospital, Semarang - Tan Hengky; Setya Budi Azhar (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Introduction. Head injury is one of trauma cases with high morbidity and mortality, with an incidence of 7.3 to 811 cases per 100.000 individuals per year and mortality ratio varying from 5.2 to 80.73 cases per 100.000 cases. Calvaria fractures that result from head injuries are often associated with risk of post-traumatic morbidity and mortality, where the incidence of post-trauma calvaria fractures is about 25% of all cases and around 10% of calvaria fractures are depressed calvaria fractures. This study was aimed to identify the characteristics of patients with depressed calvaria fractures at Dr. Kariadi General Hospital in 2020. Methods. This research is a descriptive study using secondary data from medical records. There were 30 patients with depressed calvaria fractures in January - December 2020 at Dr. Kariadi Hospital. The data is then presented in tabular form. Results. Depressed calvaria fractures in the period 2020 at Dr. Kariadi General Hospital was dominated by male (76.7%), mainly age 12-45 years old with a mean of 25.73 years old. The most common cause of depressed calvaria fractures is high velocity trauma. Minor head injury is the most common type of head injury. Depressed calvaria fractures of the frontal bone predominate in 80% of cases, with fracture depth > 1 tabula. Conclusion: There were no cases of posttraumatic infection. There were 16.7% of cases with neurological deficits at the time of discharge. There were 73.3% cases with other intracranial disorders associated with depressed calvaria fractures. Operative management is the main choice of management with most cases length of stay are 5-10 days.